PENGARUH METODE PEMBELAJARAN BRAINSTORMING TERHADAP HASIL BELAJAR MATEMATIKA SISWA - Eka Putri, Latifaturrahmi; Fitri, Haida; Aniswita; Rusdi (Prismatika: Jurnal Pendidikan dan Riset Matematika, 2023)
Based on the results of observations made by researchers in class XI MIPA at SMA Negeri 1 Banuhampu, it was found that the problem in this study was the low mathematics learning outcomes of students, this was because the learning process was dominated by teachers and students tended to be passive in learning. Seeing these problems the researcher provides a solution through the application of the brainstorming learning method in linear programming material. Because the brainstorming learning method can increase student learning activities and make learning outcomes better. This research was an experimental research with the static group comparison research design. The population in this study were 4 classes XI MIPA SMA Negeri 1 Banuhampu. Based on the research and test results of students' mathematics learning in the sample class, the data obtained were not normally distributed and were homogeneous. The calculation results obtained in the discussion through the u-test standardized z-test obtained that = 3.3784 and = 1.65. The calculation results show that . This means that the test decision H0 is rejected and H1 is accepted. So it can be concluded that there is a significant effect of the use of the brainstorming learning method on the mathematics learning outcomes of class XI MIPA students at SMA Negeri 1 Bahuhampu in the 2022/2023 academic year.